The Indicators of Effective Parenting: A Qualitative Study - Habib Jokar; Zabihollah Abbaspour; Reza Khojasteh Mehr (Kerman University of Medical Sciences, 2023)
Background: Parents are the main caregivers in raising children, and the quality and quantity of knowledge of parenting styles and child-rearing practices are essential for improving the growth, health, and correct upbringing of children. Thus, correct upbringing is one of the very important issues as it requires parental responsibility. To this end, the present study aimed to identify the components of effective parenting.Methods: This study was conducted using a conventional qualitative content analysis method. The participants were 9 family counseling specialists in Ahvaz, who were selected using homogeneous purposive sampling. The data were collected through in-depth and exploratory interviews. The collected data were analyzed using the six-step thematic analysis method proposed by Braun and Clarke.Results: The analysis of the participants' experiences revealed 5 main themes in effective parenting, including conscious knowledge, cohesion and intimacy in marital relationship, scientific application of direct and indirect parenting practices, a structured family, and creating a context for growth and availability. Conclusion: The results reported in this study can have some implications for parents in using effective child-rearing practices. Besides, family counselors and psychologists can use the results of this study to increase parents' awareness of effective parenting components and patterns by teaching the components of effective parenting to parents.